Opportunities for Mobile App-Based Adherence Support for Children With Tuberculosis in South Africa - Morse, Rachel M; Myburgh, Hanlie; Reubi, David; Archey, Ava E; Busakwe, Leletu; Garcia-Prats, Anthony J; Hesseling, Anneke C; Jacobs, Stephanie; Mbaba, Sharon; Meyerson, Kyla; Seddon, James A; van der Zalm, Marieke M; et al. (JMIR Publications, 2020)
Tuberculosis is the number one infectious cause of death globally. Young children, generally those younger than 5 years, are at the highest risk of progressing from tuberculosis infection to tuberculosis disease and of developing the most severe forms of tuberculosis. Most current tuberculosis drug formulations have poor acceptability among children and require consistent adherence for prolonged periods of time. These challenges complicate children's adherence to treatment and caregivers' daily administration of the drugs. Rapid developments in mobile technologies and apps present opportunities for using widely available technology to support national tuberculosis programs and patient treatment adherence. Pilot studies have demonstrated that mobile apps are a feasible and acceptable means of enhancing children's treatment adherence for other chronic conditions. Despite this, no mobile apps that aim to promote adherence to tuberculosis treatment have been developed for children. In this paper, we draw on our experiences carrying out research in clinical pediatric tuberculosis studies in South Africa. We present hypothetical scenarios of children's adherence to tuberculosis medication to suggest priorities for behavioral and educational strategies that a mobile app could incorporate to address some of the adherence support gaps faced by children diagnosed with tuberculosis. We argue that a mobile app has the potential to lessen some of the negative experiences that children associate with taking tuberculosis treatment and to facilitate a more positive treatment adherence experience for children and their caregivers.